Activity pattern analysis of the subthalamopallidal network under ChannelRhodopsin-2 and Halorhodopsin photocurrent control. (September 2020) - Zhang, Honghui; Yu, Ying; Deng, Zichen; Wang, Qingyun
Highlights: Two computational models for ChannelRhodopsin-2 (ChR2) are tested and verified: three-state and four-state models. Two types of proteins are employed and investigated: excited ChannelRhodopsin-2 (ChR2) and inhibited Halorhodopsin (NPHR). Two prototype network architectures of STN-GPE network are studied and compared: The sparsely coupled network and the tightly coupled network. Abstract: This paper incorporates the neural photostimulation to model firing activities of the subthalamopallidal network from basal ganglia, and the emphasis is to explore the possible effects of light-gated cation membrane channel on neural system, especially to estimate the probability of therapeutic strategy in neurological disorders. Under excitatory and inhibitory photosensitive protein, we mainly study the firing rhythms of subthalamic nucleus (STN) and also external segment of globus pallidus (GPe) in different coupling modes, which is closely related with somatic movement. Firstly, the applicability of earlier proposed three-state and four-state models of ChannelRhodopsin-2 (ChR2) has been tested and verified through the reaction of single GPe neuron, together with the response of neurons to Halorhodopsin (NpHR). Then we analyze the firing patterns of neural population under two prototype network architectures respectively, being considered as different types and degrees of morbidity. The sparsely coupled network can produce six general classes of sustained firing patterns with little regularity, while the tightly coupled network can provide five different general waveforms with high correlation, including cluster synchronization of in-phase and anti-phase. Most noteworthy, with the concern of ultrafast optogenetic control, we find the pathological firing patterns can be destroyed and even eliminated under appropriate conditions, which can give some enlightenment for the treatment and regulation of Parkinson's disease and other motor neurone disease related to basal ganglia.